Iodized Salt: A Risk Factor for Hyperthyroidism - Samia Sarwar , Muhammmad Aslam , Muhammad Amin Waqar ,Mazhar Hussain , Idrees Farooq Butt, (Journal of Rawalpindi Medical College, 2013)
Background: To evaluate dietary use of iodized salt as a risk factor for hyperthyroidism in people living in iodine deficient areas of Pakistan. Methods: In this case control study, patients (n=150), 50 male and 100 female, aged 35-75 years, from Northern region of Pakistan, with goiter and hyperthyroidism; and healthy control group (n=100), 32 males and 68 females aged 35-75 years from same region, were selected by probability convenience sampling. The patient and control group were interviewed regarding use of iodized salt. History and physical examination of patient group was done for assessment of symptoms and goiter. Thyroid stimulating hormone (TSH) and free thyroxin (FT4) were analyzed in Patient and Control group both. Results: The study revealed 67% prevalence of goiter between 46-55 years in patient group with female predominance. Grade two multinodular goiters were followed by Solitary nodules and diffuse goiter in patient group. The residents of Azad Jammu and Kashmir region were more affected in patient group. Mean FT4 was 46.5+/-22 pmol/L in patients and 16.036+/-8 in controls. Mean TSH was 0.099+/-0.03 and 1.44061+/-0.39 in patients and controls respectively. The family history for thyroid disease was positive in 72% of patients and 56% in controls. The relative risk in iodized salt exposed vs. non exposed individuals showed Odd ratio of 5.2. Conclusion: Iodized salt is a risk factor for development of hyperthyroidism in iodized salt users living in iodine deficient areas of Pakistan.